2010
DOI: 10.1021/jm100093p
|View full text |Cite
|
Sign up to set email alerts
|

“Viologen” Dendrimers as Antiviral Agents: The Effect of Charge Number and Distance

Abstract: A series of "viologen" derivatives (4,4'-bipyridinium salts) carrying between 1 and 90 charges per molecule have been prepared and investigated for their activity against human immunodeficiency virus (HIV), herpes simplex virus (HSV), vesicular stomatitis, Punta Toro virus, Sindbis virus, Reovirus, and respiratory syncytial viruses. In general, most of the compounds showed good activities against HIV-1 (strain III(B)). In particular, compound 36 exhibited the highest in vitro activity and selectivity index aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 30 publications
0
64
0
Order By: Relevance
“…Recent studies have shown that incorporating viologen units into the dendritic backbone can yield new positive biological properties. Several polycationic viologen-based dendrimers were tested for antiviral activity against human immunodeficiency virus (HIV-1), herpes simplex virus (HSV), vesicular stomatitis, Punta Toro virus, Sindbis virus, reovirus, and respiratory syncytial viruses and were shown to be good inhibitors of HIV-1 [25]. Ciepluch et al [26] studied eight novel dendrimers with both phosphorus groups and viologen units in their structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that incorporating viologen units into the dendritic backbone can yield new positive biological properties. Several polycationic viologen-based dendrimers were tested for antiviral activity against human immunodeficiency virus (HIV-1), herpes simplex virus (HSV), vesicular stomatitis, Punta Toro virus, Sindbis virus, reovirus, and respiratory syncytial viruses and were shown to be good inhibitors of HIV-1 [25]. Ciepluch et al [26] studied eight novel dendrimers with both phosphorus groups and viologen units in their structure.…”
Section: Introductionmentioning
confidence: 99%
“…[88,89] Two types of dendritic viologens, namely 'comb-branched' (23) and 'spheroidal' (24), were investigated for their antiviral properties. The spheroidal viologen dendrimers (24) were shown to be more effective than comb-branched dendrimers.…”
Section: Dendritic Polymer-based Entry Inhibitorsmentioning
confidence: 99%
“…The spheroidal viologen dendrimers (24) were shown to be more effective than comb-branched dendrimers. [88] Furthermore, the viologen dendrimers caused selective inhibition of HIV-1 but showed little or no inhibitory potency against the HIV-2 ROD strain or against other viruses. In a subsequent study, Asaftei et al proposed that the thymine end-capped dendrimer viologens have a dual advantage.…”
Section: Dendritic Polymer-based Entry Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3,4] In a completely different field it can be also mentioned that structure-activity relationships of a series of viologen units and dendrimers as antiviral agents were recently reported, pointing out an unexpected biological aspect of viologen dendrimers as novel HIV-1 replication inhibitors. [5] Up to now, viologen units were incorporated at the focal point, [4,6] or at the core, the branches, and the periphery [7] of a very few types of purely organic dendrimers. [8] Similarly, phosphorus dendrimers, and especially those we are developing, are extremely versatile macromolecules with unique properties and applications.…”
Section: Introductionmentioning
confidence: 99%